Arctiinae (Lepidoptera, Arctiidae) coletados em unidades de conservação estaduais do Rio Grande do Sul, Brasil - TESTON, José Augusto (2013)
Arctiinae (Lepidoptera, Arctiidae) collected in protected unities in Rio Grande do Sul State, Brazil. The objective of this work was to analyze the composition of the Arctiinae communities at Parque Estadual do Espigão Alto (Barracão), Parque Estadual de Rondinha (Sarandí), Parque Estadual do Turvo (Derrubadas) and at Reserva Biológica de Ibirapuitã (Alegrete). Ten light traps were used to collect the lepidopterous from November/2000 to February/2001, sampling one nigth per area. The lepidopterous were identified at subfamily and tribe levels and, when it was possible, at genera and species levels. A total 5,969 Arctiinae belonging to 137 morpho species, distributed in 6 tribes were collected.